2004
DOI: 10.1117/12.568751
|View full text |Cite
|
Sign up to set email alerts
|

Development of multilayer coatings (Ni/C-Pt/C) for hard x-ray telescopes by e-beam evaporation with ion assistance

Abstract: A number of X-ray astronomical missions of near future (XEUS, Constellation-X, SIMBOL-X, HEXIT-SAT, NEXT) will make use of hard X-ray (10-100 keV) optics with broad-band multilayer coatings. To this aim we are developing a multilayer deposition technique for large substrates based on the e-beam deposition technique, improved by the implementation of an ion beam assistance device, in order to reduce the interfacial roughness and improve the reflectivity. The e-beam deposition with ion assistance keeps the film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Another advantage of e-beam evaporation is the uniform coating over large surfaces, like mandrels used for mirror shell replication. The main drawback of this method is the evaporation rate instability; very good results were, indeed, obtained in terms of peak reflectivity 12 . Sputtering processes are suitable to deposit compact and uniform films with good optical and mechanical properties: multilayers deposited by sputtering (like sample C) exhibit a good smoothness and durability in time, an important requirement for space telescopes with long lifetime.…”
Section: Choice and Description Of Analyzed Samplesmentioning
confidence: 99%
“…Another advantage of e-beam evaporation is the uniform coating over large surfaces, like mandrels used for mirror shell replication. The main drawback of this method is the evaporation rate instability; very good results were, indeed, obtained in terms of peak reflectivity 12 . Sputtering processes are suitable to deposit compact and uniform films with good optical and mechanical properties: multilayers deposited by sputtering (like sample C) exhibit a good smoothness and durability in time, an important requirement for space telescopes with long lifetime.…”
Section: Choice and Description Of Analyzed Samplesmentioning
confidence: 99%
“…They are also suited as monochromators for Cu Kα radiation in virtue of low divergence of the reflected beam and the superior suppression of Cu Kβ radiation678. Moreover, depth-graded Ni/C multilayers are used in astronomical telescopes in hard X-ray region910.…”
mentioning
confidence: 99%
“…To address these problems, many authors have suggested covering heavy materials with a thin layer of a low-Z material, such as C or B 4 C [14][15][16][17] or even an organic compound (polyethylene 18 ). As shown in Fig.…”
Section: Design Of Grazing Incidence Mirrorsmentioning
confidence: 99%